Undergraduate Students’ Perceptions on Educational Level Language Use and Social Media’s Role in Communication - Haswani, Fahri; Syahputri, Rina Trie; Sianipar, Jose Christian; Girsang, Ami; Manurung, Ribka Hawkins (Universitas Negeri Medan, 2025)
As language usually shapes people’s socio-economics status, people has become opinionated that what education degree/level an individual has can be seen by the way they communicate. This paper explores whether it is also true for higher education people use less standardized language when speaking in daily life and if social media helps low-educated individuals to speak as formal as high-educated ones. This paper employed a mixed-method approach with 5 participants from the same level of education: undergraduate students. Findings indicate that indeed people with higher education level usually has distinctive style of communication compared to those with lower education yet it depends on the context of situation. In addition to the communication style, the proability of social media helping to form formal communication for lower educated individual is possible as they expose people to all kinds of information, including language. This research is expected to contribute to raising awareness about the relationship of education and communication style.